SARS-CoV-2 spike protein antibody titers after the fourth dose of BNT162b2 vaccine among Japanese patients undergoing hemodialysis: a single-center study - Watanabe, Shun; Sawano, Toyoaki; Saito, Hiroaki; Ozaki, Akihiko; Wakui, Masatoshi; Zhao, Tianchen; Yamamoto, Chika; Kobashi, Yurie; Kawamura, Takeshi; Sugiyama, Akira; Nakayama, Aya; Kaneko, Yudai; et al. (Frontiers in Immunology, 2024)
Patients undergoing hemodialysis are particularly vulnerable to severe outcomes of SARS-CoV-2 infection, with mortality rates higher than that of the general population. Vaccination reduces the risk of adverse outcomes, with booster doses being particularly beneficial. However, limited data are available on the effectiveness of subsequent vaccinations or their effect on increasing antibody levels. This single-center study aimed to investigate changes in SARS-CoV-2 IgG antibody titers following the fourth vaccination among 28 patients undergoing hemodialysis. Blood tests were conducted at various intervals post-vaccination, with a focus on identifying factors associated with antibody levels. The IgG antibody levels rapidly increased by Day 7 post-vaccination, with a median time to peak of 11 days. Antibody titers tended to be higher in male patients than in female patients. This study sheds light on the immune response to the fourth vaccination in patients undergoing hemodialysis. As this study included a small sample size, with a short observation period, further research is warranted to comprehensively understand the effectiveness of vaccination and the benefits of additional doses of vaccine.